2010
DOI: 10.1016/j.cell.2010.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Requires Sequestration of Glycogen Synthase Kinase 3 inside Multivesicular Endosomes

Abstract: SUMMARY Canonical Wnt signaling requires inhibition of Glycogen Synthase Kinase 3 (GSK3) activity, but the molecular mechanism by which this is achieved remains unclear. Here we report that Wnt signaling triggers the sequestration of GSK3 from the cytosol into multivesicular bodies (MVBs), so that this enzyme becomes separated from its many cytosolic substrates. Endocytosed Wnt co-localized with GSK3 in acidic vesicles positive for endosomal markers. After Wnt addition, endogenous GSK3 activity decreased in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

53
769
6
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 636 publications
(863 citation statements)
references
References 66 publications
53
769
6
3
Order By: Relevance
“…(2) Because GSK3 levels do not overtly decrease during Wnt signaling, it requires a mechanism for GSK3 subsequently to escape MVBs, which normally shuttles the cargo to lysosomes for degradation. (3) It suggests that genes involved in MVB formation are required for Wnt signaling, for which supporting evidence exists in Xenopus but not in Drosophila (Piddini et al 2005;Rives et al 2006;Seto and Bellen 2006;Taelman et al 2010). (4) It predicts that most GSK3 substrates (in fact, 20% of cellular proteins) in addition to b-catenin are under Wnt regulation (Taelman et al 2010), thus departing from the prevailing view that roles of GSK3 in Wnt and other signaling (such as insulin) pathways are insulated from one another.…”
Section: Wnt Receptors and Signaling Mechanismsmentioning
confidence: 72%
See 2 more Smart Citations
“…(2) Because GSK3 levels do not overtly decrease during Wnt signaling, it requires a mechanism for GSK3 subsequently to escape MVBs, which normally shuttles the cargo to lysosomes for degradation. (3) It suggests that genes involved in MVB formation are required for Wnt signaling, for which supporting evidence exists in Xenopus but not in Drosophila (Piddini et al 2005;Rives et al 2006;Seto and Bellen 2006;Taelman et al 2010). (4) It predicts that most GSK3 substrates (in fact, 20% of cellular proteins) in addition to b-catenin are under Wnt regulation (Taelman et al 2010), thus departing from the prevailing view that roles of GSK3 in Wnt and other signaling (such as insulin) pathways are insulated from one another.…”
Section: Wnt Receptors and Signaling Mechanismsmentioning
confidence: 72%
“…DIX oligomerization/polymerization is proposed to provide a DVL platform for dynamic assembly of protein -protein interactions of low avidity, such as between DVL and Axin (Schwarz-Romond et al 2007b), and is a main underpinning for the receptor "signalosome" hypothesis (Bilic et al 2007) (see below). However, some have suggested that the DVL "aggregates" (or "dots" under microscopes) represent endocytic vesicles (Capelluto et al 2002;Taelman et al 2010). The simplest model states that DIX and PDZ domains, but not DEP, are required for Wnt/b-catenin signaling, as seen in some overexpression studies.…”
Section: The Wnt -Fzd -Lrp5/6 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Le tube intestinal présente pourtant une architecture fascinante, nettement conditionnée par sa fonction, qui est assurée par un agencement de villosités et de courbures servant à maximiser la surface d'absorption des nutriments. Dans un article récem-ment publié dans la revue Nature [2], nous avons étudié la morphogenèse des boucles intestinales. Une démarche interdisciplinaire en biologie et en physique, à la fois expérimentale et théorique, nous a permis de montrer que l'enroulement intestinal a pour origine un équilibre tissulaire de forces élastiques.…”
Section: Effets De La Voie Wnt Sur Les Cibles De La Kinase Gsk3unclassified
“…Cependant le mécanisme exact par lequel la voie Wnt inhibe l'activité de cette kinase était jusqu'à présent mal compris. Dans une étude récente [2], nous avons montré que l'activation de la voie Wnt induit la séquestration de GSK3 à l'intérieur de vésicules intracellulaires appelées endosomes multivésiculaires (MVE).…”
unclassified